English Sound System: A Phonological Perspective Understanding Pronunciation Challenges and Teaching Strategies for Non-Native Speakers - Dhea Salsabila; Izzati Amirah Sari; Rafly Raja Ghazali; Yani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study looks at the English sound system from a phonological standpoint, emphasizing successful teaching strategies and the difficulties non-native speakers have pronouncing words correctly. This study examines the effects of native language interference, identifies particular phonological challenges, and assesses instructional methods for improving pronunciation using qualitative research with fourth-semester English education students. The results show that although explicit phonetic teaching greatly helps pupils, they still struggle to manage spelling-pronunciation inconsistencies and discern vowel lengths. By offering insights into phonological learning processes and suggesting evidence-based teaching strategies, the research advances the field of applied linguistics. Although individual sound distinctions require tailored treatments, the results show that systematic pronunciation education improves student confidence and communicative skills.